A set of 13 multiplex PCRs of specific microsatellite markers as a tool for QTL detection in gilthead seabream (Sparus aurata L.). (27th January 2014) - Negrín‐Báez, Davinia; Navarro, Ana; Lee‐Montero, Ivonne; Afonso, Juan M; Sánchez, Juan J; Elalfy, Islam S; Manchado, Manuel; Sánchez, José A; García‐Celdrán, Marta; Zamorano, María J
Abstract: The growth and consolidation of the gilthead seabream ( Sparus aurata ) industry require improvement based on permanent and cumulative aspects, such as those derived from genetic breeding programmes. Marker Assisted Selection (MAS) by Quantitative Trait Loci (QTL) can be usefully implemented with the appropriate tools. In this study, 138 microsatellite markers from the genetic map of gilthead seabream were redesigned to be amplified under the same PCR conditions. A final set of 13 multiplex PCRs (named ReM sa ) with 106 of these markers was developed to cover 100% of the linkage groups. These effective multiplex PCRs enable to optimize QTL searching with a critical reduction in costs and errors. Results showed that the mean value of the number of alleles for 106 markers was 6.9. The mean observed heterozygosity ranged from 0.53 to 0.86, and 74.5% of markers were highly informative according to their polymorphic information content. The correct inheritance and segregation of alleles of each locus was confirmed after genotyping 62 individuals of a full‐sib family by these multiplex PCRs. In addition, genetic features of the 20 microsatellite markers that worked correctly but were not included in any multiplex PCR are also reported to provide geneticists with the possibility of including them in more comprehensive screening studies.